Determinants of Adherence to National Infant Feeding Guidelines by Black Mothers Living with HIV - Hannan, Jean (Ethn Dis, 2021)
OBJECTIVE: Worldwide, 160,000 children were newly infected with HIV in 2018; half of these were infected through breastfeeding. Infant feeding guidelines are distinct depending on each country’s resources and national or sub-national guidelines. Because of divergent guidelines, the best infant feeding approach to prevent mother-to-child transmission can become unclear. The purpose of this study was to examine the sociocultural and psychosocial factors related to adherence to infant feeding guidelines through a city-level, North-South comparison of Black mothers living with HIV in Nigeria, Canada, and the United States. DESIGN: Using a cross-sectional multi-country survey, a convenience sample of 690 mothers were recruited from June 2016 - December 2019. Socio-cultural and psychosocial factors influencing infant feeding practices were measured. RESULTS: Using binary logistic regression, infant feeding attitudes (OR = 1.10), motherhood experiences (OR = 1.08), low hyper-vigilance score (OR = .93), paternal support (OR = 1.10) and perception that the health care provider supported adherence to infant feeding guidelines (OR = 2.43) were associated with guideline adherence. Mothers who had cultural beliefs that were inconsistent with infant feeding guidelines and mothers with low incomes (OR = 2.62) were less likely adherent with their country’s guidelines. CONCLUSION: City-level factors were not found to influence adherence to infant feeding guidelines; however, socio-cultural and psychosocial factors at community, family and individual levels were significant. Policy formulation and targeted interventions must be cognizant of cultural expectations of motherhood and mindful of psychosocial determinants of adherence to infant feeding guidelines.